Telescope inaccuracy model based upon satellite laser ranging data - Zhaborovskyy, V.P.; Pap, V.O.; Medvedsky, M.M.; Choliy, V.Ya. (Advances in Astronomy and Space Physics, 2013)
In this paper, a new approach to constructing a telescope pointing model is described. Procedures of data collection, data processing, and model construction are presented. Telescope encoder countings, obtained during satellite laser ranging, are used as input data for the construction of the model. The model is presented as a harmonical series with frequencies obtained by the maximum entropy spectral analysis method.